Education and Investment in Human Capital - Weisbrod, Burton A. (Journal of Political Economy, 1962)
As technological developments have altered production techniques, types of mechanical equipment, and varieties of outputs, society has begun to recognize that economic progress involves not only changes in machinery but also in men – not only expenditures on equipment but also on people. Investment in people makes it possible to take advantage of technical progress as well as to continue that progress. Improvements in health make investment in education more rewarding by extending life expectancy. Investment in education expands and extends knowledge, leading to advances which raise productivity and improve health. With investment in human capital and non-human capital both contributing to economic growth and welfare and in what is probably an interdependent manner, more attention should be paid to the adequacy of the level of expenditures on people.